Global Modeled Sinking Characteristics of Biofouled Microplastic - Lobelle, Delphine; Kooi, Merel; Koelmans, Albert A.; Laufkötter, Charlotte; Jongedijk, Cleo E.; Kehl, Christian; van Sebille, Erik (Journal of geophysical research. Oceans, 2021)
Microplastic debris ending up at the sea surface has become a known major environmental issue. However, how microplastic particles move and when they sink in the ocean remains largely unknown. Here, we model microplastic subject to biofouling (algal growth on a substrate) to estimate sinking timescales and the time to reach the depth where particles stop sinking. We combine NEMO‐MEDUSA 2.0 output, that represents hydrodynamic and biological properties of seawater, with a particle‐tracking framework. Different sizes and densities of particles (for different types of plastic) are simulated, showing that the global distribution of sinking timescales is largely size‐dependent as opposed to density‐dependent. The smallest particles we simulate (0.1 μm) start sinking almost immediately around the globe and their trajectories take the longest time to reach their first sinking depth (relative to larger particles). In oligotrophic subtropical gyres with low algal concentrations, particles between 1 and 0.01 mm do not sink within the simulation time of 90 days. This suggests that in addition to the comparatively well‐known physical processes, biological processes might also contribute to the accumulation of floating plastic (of 1–0.01 mm) in subtropical gyres. Particles of 1 μm in the gyres start sinking largely due to vertical advection, whereas in the equatorial Pacific they are more dependent on biofouling. The qualitative impacts of seasonality on sinking timescales are small, however, localized sooner sinking due to spring algal blooms is seen. This study maps processes that affect the sinking of virtual microplastic globally, which could ultimately impact the ocean plastic budget. Plain Language Summary It is a well‐known global issue that the sea surface is polluted with microplastic, however, understanding when and how floating plastic can sink is still limited. Biofouling (algal attachment on an object’s surface) is one process that can cause microplastic’s density to be larger than its surrounding seawater and therefore sink. Microplastic experiments in the oceans are hard to execute so we generate simulations by releasing virtual particles globally at the sea surface. We include seawater and algal properties from a general circulation model and examine how long it takes for biofouled particles to sink. The smallest particles we use (0.1 microns) sink almost immediately globally, since a small number of attached algae is enough to increase their density. Coincidentally, in regions where plastic is known to accumulate due to currents converging (the five gyres), algae is scarce and hence larger particles (10 microns to 1 mm) remain afloat during our 90 days simulations. Our results also show that initial sizes of microplastic affect sinking timescales more than their initial density (where density represents different types of plastic). Our research aims to further understand how biofouling can affect sinking of microplastic globally, ultimately bringing us closer to understanding where plastic ends up in oceans. Key Points Sinking timescales of virtual particles subject to biofouling are more dependent on the initial size of particles than initial density Low algal presence in subtropical gyres and minimal biofouling can contribute to particles between 1 and 0.01 mm remaining at the surface Modeled biofouled particles of 0.1 microns start sinking almost immediately and show a global median sinking timescale of one day